Effect of Different Gradual Exercises on Physiological Responses - ARAI, Mitsuo; KASHIMA, Kazue; WATANABE, Masatoshi; MONDEN, Masahisa; INO, Kuniko (Journal of exercise physiology, 1988)
Effects of two different load exercise generated by the bicycle ergometer, gradual load (10W/min) and sudden load (99W/min), on physiological responses were examined concerning RPP, blood pressure, and heart rate. Subjects were 41 healthy young women, whose average age being 20.5±2.3. With respect to heart rate, it reached 95% of estimated maximum heart rate in the gradual load exercise, but only 75% in the sudden load exercise. Results obtained in the sudden load exercise test induced equations permitted to give the estimated values of the maximum heart rate, blood pressure, and RPP. There was little correlation between the maximum heart rate and the maximum blood pressure. Under the condition of aerobic work, it might be necessary for avoiding risks that not only heart rate but also both RPP and blood pressure should be taken into consideration.